PENGARUH LINGKUNGAN KAMPUS DAN EMOTIONAL INTELLIGENCE TERHADAP MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI ADMINISTRASI PENDIDIKAN FKIP UNIVERSITAS JAMBI - Risna Fadillah; Aprillitzavivayarti Aprillitzavivayarti; Robi Hendra (Jurnal Manajemen Pendidikan, 2026)
This study aims to determine the influence of the campus environment and emotional intelligence on the learning motivation of students in the Educational Administration Program at the Faculty of Teacher Training and Education, University of Jambi. The study employed a quantitative research design using a survey approach. The population for this study consisted of all students in the Educational Administration Program at the Faculty of Teacher Training and Education, University of Jambi, comprising the 2022–2025 cohorts, with a total sampling technique. Data were collected via a distributed questionnaire, and data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results of the study indicate that: (1) the campus environment has a positive and significant influence on students’ learning motivation with a p-value of 0.000 < 0.05 and a T-statistic value of 5.578 > 1.96. (2) emotional intelligence has a positive and significant influence on students’ learning motivation with a p-value of 0.000 < 0.05 and a T-statistic of 6.635 > 1.96. (3) Simultaneously, the campus environment and emotional intelligence influence student learning motivation. These findings indicate that the campus environment and emotional intelligence play a crucial role in enhancing the learning motivation of students